Phylogeny and evolution of the angiosperms. (2018) - Soltis, Douglas E; Soltis, Pamela S; Endress, Peter K; Chase, Mark W, 1951-; Manchester, Steven R, 1956-; Judd, Walter S; Majure, Lucas C, 1981-; Mavrodiev, Evgeny
No abstract available